NAVIGATING REGIONAL AUTONOMY: AN INTEGRATED FRAMEWORK OF LEADERSHIP AND POLICY INNOVATION IN LOCAL GOVERNANCE - Andi Rahmat Nizar Hidayat; Tri Cahyo Nugroho (Politeknik STIA LAN Makassar, 2026)
This study aims to analyze the relationships among regional leadership, public policy innovation, and regional autonomy within the context of governance transformation. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, this study synthesizes recent literature to identify theoretical patterns and conceptual alignments among the main variables. The findings indicate that regional leadership functions as a strategic node that unlocks autonomous space, while policy innovation serves as a mechanism that transforms authority into enhanced governance performance and policy effectiveness. In this context, regional autonomy plays a dual role: as an enabler that creates opportunities for innovation and as a structural constraint that limits innovation through regulations and institutional capacity. Thematically, the study identifies a shift from transformational leadership to adaptive and collaborative leadership, alongside a transition from technology-based innovation toward collaborative governance. Based on this synthesis, the study develops an integrated analytical framework called the Transformation Loop. This framework connects five key variables: leadership, regional autonomy, policy innovation, governmental performance, and policy effectiveness within a dynamic and reciprocal relationship. The novelty of this study lies in the integration of three major dimensions into a single conceptual model capable of explaining regional governance transformation systematically rather than partially. These findings contribute to the advancement of public administration literature and offer practical implications for strengthening strategic leadership and policy innovation in the autonomous regions.